Training on Rehabilitation of Rasuna Said's House as a Cultural Heritage Building, in Agam District, West Sumatera - I Nengah Tela; Riki Adriadi; Jonny Wongso; Fielda Roza (Budapest International Research and Critics University, 2022)
A sizable improvement was made in 2013 with the funding source coming from Garuda Indonesia's Corporate Social Responsibility (CSR). At that time the repairs carried out included strengthening the second floor by coating multiplex with a thickness of 12 mm, painting, repairing windows and doors on the second floor. Massive changes were made on the first floor, namely the demolition of all the walls of the rooms, dismantling the wooden floors and replacing them with ceramic floors. The rehabilitation training at this PKM was observing Rasuna said's house which significantly explained that the main building or the middle building on the first floor had two windows, while the second floor had three windows. The function of this window is to enter sunlight as room lighting from sunlight during the day, besides that the window also functions as a regulation of air circulation from the right side. The floor plan of Rasuna Said's house is rectangular, extending towards the back with a length of 26 m, a width of 9.9 m. The floor plan of the building is above the ground with a slope towards the back of approximately 2 m, from the road to the boundary of the rear building (kitchen building). The building plan consists of several rooms, namely; reception room/porch, living/main room, back room, as well as the front yard and fence. The reception room is the front room, on the left side of the foyer there is one room. Furthermore, the main room is positioned in the middle, from this room you can continue to the second floor and to the back room/kitchen.